2005
DOI: 10.1016/j.cardiores.2005.05.010
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein induces tissue factor expression and promotes smooth muscle and endothelial cell proliferation

Abstract: These data indicate that CRP exerts direct effects on ECs and SMCs by promoting proliferation and TF expression and support the notion that CRP, besides representing a marker of inflammation, is an effector molecule able to induce a pro-atherothrombotic phenotype in cells of the vessel wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
105
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 45 publications
5
105
0
6
Order By: Relevance
“…Furthermore, we have previously shown in vivo that CRP augments NFκb activity in rat pouch macrophages. In this paper, in support of the work of Cirillo et al [36], we show that inhibition of NFκb activity with CAPE, resulted in significant inhibition of CRP-induced TF activity in vivo. Furthermore, using three scavengers of ROS, we demonstrate a link between CRPinduced superoxide release and TF activity, since all three inhibitors significantly abrogate CRP-induced TF activity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, we have previously shown in vivo that CRP augments NFκb activity in rat pouch macrophages. In this paper, in support of the work of Cirillo et al [36], we show that inhibition of NFκb activity with CAPE, resulted in significant inhibition of CRP-induced TF activity in vivo. Furthermore, using three scavengers of ROS, we demonstrate a link between CRPinduced superoxide release and TF activity, since all three inhibitors significantly abrogate CRP-induced TF activity.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, CRP also induced TF expression in both cell types in a dose-dependent fashion, exerting its effect at the transcriptional level, as demonstrated by semiquantitative and by real-time PCR. Activation of the transcription factor, NFκb, by CRP was demonstrated by EMSA and they also demonstrated suppression of TF expression by the NFκb inhibitor, pyrrolidine-dithiocarbamate ammonium [12,36]. In rat pouch macrophages, in vivo, we show for the first time that CRP-induced TF is inhibited by inhibitors to p38MAPK and JNK, but not ERK inhibitor.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…15 Therefore CRP might play a role not only in inflammation but also in atherothrombosis. 16,17 In this investigation we looked at the two phenomena from the same angle and wanted to rest our hypothesis in that direction. We had hypothesized that if CRP plays an important role in thrombus development we should be detecting high levels of hs-CRP on admission day in patients with left ventricular thrombus (LVA).…”
Section: Discussionmentioning
confidence: 99%
“…Both the p50 and p60 subunits of NFkB play a role in the transcription of CRP, 29 which appeared to have proatherogenic properties through upregulation of expression of AT 1 receptor 30 and activation of vascular smooth muscle cells in some studies. 31,32 Over 30 studies have reported that higher plasma levels of CRP are associated with higher risks of CHD, 33 but other studies have not been to able to confirm these associations, 34,35 and there is uncertainty as to whether these associations are causal. Fibrinogen has been observed to regulate to NFkB activation and the expression of chemokines in vascular endothelial cells, 36 but for it too there is uncertainty about the nature of the relationship with vascular disease.…”
Section: Marker and Genotypementioning
confidence: 99%